Fabrication of a Targeted Drug Delivery System from a Pillar[5]arene‐Based Supramolecular Diblock Copolymeric Amphiphile for Effective Cancer Therapy. (4th July 2016) - Yu, Guocan; Yu, Wei; Shao, Li; Zhang, Zhihua; Chi, Xiaodong; Mao, Zhengwei; Gao, Changyou; Huang, Feihe
Abstract : Effective cancer therapy will profit from the development of sophisticated drug delivery systems with stimuli‐responsive properties that are capable of delivering therapeutic doses to the active sites, while minimizing the accumulation of highly toxic drugs in off‐target sites. Herein, the fabrication of a pillararene‐based amphiphilic supramolecular diblock polymer (P5‐PEG‐Biotin ⊃PCL‐C2 V ) based on the host–guest recognition between a water‐soluble pillar[5]arene and a viologen salt is reported.P5‐PEG‐Biotin ⊃PCL‐C2 V self‐assembles into polymersomes, which are utilized as drug delivery vehicles for doxorubicin hydrochloride (DOX). Decorated by the biotin groups, these smart nanocarriers deliver the anticancer drug preferentially to biotin receptor over‐expressing cancer cells. After internalization by the cells, the viologen group is reduced into the cationic radical state by the intracellular reductase NAD(P)H, leading to the release of the loaded DOX by the disassembly of the polymersomes. More importantly, DOX‐loaded polymersomes maintain the therapeutic efficacy towards cancerous HeLa cells, while exhibiting relatively low cytotoxicity towards normal HEK293 cells. In vivo studies reveal that the DOX‐loaded supramolecular polymersomes prolong the circulation time in the bloodstream, promote the antitumor efficacy and reduce the systematic toxicity of the drug through flexible and modular supramolecular strategy. Abstract : A reduction‐sensitive supramolecular diblock polymer is fabricated based on the molecular recognition motif between a novel water‐soluble pillar[5]arene and a viologen salt. It self‐assembles into polymersomes in water, which are successfully used in targeted drug delivery. In vitro and in vivo experiments demonstrate that these polymersomes can be applied in effective cancer treatment.